2016
DOI: 10.1371/journal.pone.0159674
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Circulation Time to Assess Right Ventricular Dysfunction in Pulmonary Embolism: A Retrospective Pilot Study

Abstract: ObjectiveTo optimize enhancement of pulmonary arteries and facilitate diagnosis of pulmonary embolism (PE), modern computed tomography angiography (CTA) contains a contrast bolus tracking system. We explored the diagnostic accuracy of the time-intensity curves given by this automated system to identify right ventricular dysfunction (RVD) in acute PE.Methods114 CTAs with a diagnosis of PE were reviewed. RVD was defined as right-to-left ventricular diameter ratio of 1 or greater. Four parameters on time-intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…For example, in a study by Lin et al (15) on 71 patients with acute PE, both bolus curve upslope time > 6 seconds and 50% downslope time > 6 seconds predicted PE mortality. In line with our findings, John et al (26) concluded that variables which were related to the time-intensity curve were not accurate enough for identifying right ventricular dysfunction in 114 patients with PE. One possible explanation for this inconsistency is that the right ventricular dysfunction is more likely to occur in patients with central PE, in whom the main pulmonary vasculature becomes acutely obstructed (15).…”
Section: Discussionsupporting
confidence: 84%
“…For example, in a study by Lin et al (15) on 71 patients with acute PE, both bolus curve upslope time > 6 seconds and 50% downslope time > 6 seconds predicted PE mortality. In line with our findings, John et al (26) concluded that variables which were related to the time-intensity curve were not accurate enough for identifying right ventricular dysfunction in 114 patients with PE. One possible explanation for this inconsistency is that the right ventricular dysfunction is more likely to occur in patients with central PE, in whom the main pulmonary vasculature becomes acutely obstructed (15).…”
Section: Discussionsupporting
confidence: 84%
“…The Ct was first introduced as a clinical test to assess heart failure (HF) nearly a century ago (Blumgart and Weiss 1927, 1928, Blumgart 1931. While rarely being used in the current era, its core concept that the Ct is mainly influenced by cardiac output and central blood volume is still utilized in modern medicine particularly with advanced imaging techniques (Puskas and Schuierer 1996, Muller et al 2000, Shors et al 2003, Bae 2010, John et al 2016. Similar to intravenous dyes that have been used as indicators for Ct measurement in the past, O 2 can be used as an indicator allowing for Ct measurement in the presence of dynamic O 2 change (Wexler et al 1946, Kasravi et al 1998.…”
Section: Introductionmentioning
confidence: 99%